Profitability of Agricultural Enterprises in Ukraine (On the Case of Lviv Region): Assessment of Trends and Interdependencies - Shmatkovska, Tetiana О.; Шматковська, Тетяна Олександрівна; Stashchuk, Olena V.; Стащук, Олена Володимирівна (British Journal of Economics, Management & Trade, 2017)
The main objectives of the study are generalization of the economic essence of the process of profitability formation, discovery of its tendencies and conditions of the agricultural producers in Lviv region. The research was conducted basing on the results of the activity of agricultural enterprises, issued by Main Statistic Administration in Lviv region in 2009 – 2013. The paper determines that profit of agricultural enterprises is the source of its development through reinvestment and is also the basis of stable activity and fulfils a social function in the context of providing employment for rural population. The article proves that the profitability of an agricultural enterprise is its economic state, that displays the realized and potential ability to generate a positive financial result from the implementation of both the main (related to agricultural production), and the whole business. According to results of the research of profitability of the agricultural producers in Lviv region for 2009 – 2013, the instability and heterogeneity of their development, manifested in large variation of parameters of profitability, were detected. The article proves that the application of special preferential tax treatment influences on the profitability of agricultural enterprises positively but not sufficienty.
Keywords: Profit; the profitability of agricultural enterprises; state financial support of profitability; preferential tax treatment; a multifactorial regression analysis